Toward an Understanding of Parental Views and Actions on Social Media Influencers Targeted at Adolescents: The Roles of Parents’ Social Media Use and Empowerment - Lin, Meng-Hsien; Vijayalakshmi, Akshaya; Laczniak, Russell (Frontiers in Psychology, 2019)
Recent studies suggest that adolescents are spending significant amounts of time on social media. Brands are taking advantage of this fact and actively using social media to reach adolescent consumers, primarily via social media influencers. Adolescents consider the sponsored brand posts by social media influencers to be trustworthy and honest, thus reducing their critical evaluation of the ads. While several researchers have pointed to the critical role parents play in their adolescents becoming digitally literate and empowered, there is little understanding of parental views and drivers of parental views on social media influencers and means by which they mediate their adolescents’ exposure to social media influencers. Our specific research questions are (a) how does parents’ use of social media relate to their attitudes toward and mediation of social media influencers and (b) what is the role of psychological empowerment in enabling the relationship? Through a survey of approximately 200 mothers of adolescents (between the ages of 11 and 17 years), we examine how parents’ social media usage (active or passive) is related to their views toward social media influencers and mediation of social media influencers. We find that active (vs. passive) use of social media by parents led to them significantly (vs. not significantly) mediate social media influencers’ impact. Passive (vs. active) use of social media led to parents having a significant (vs. not significant) positive view of social media influencers. We explain this direct relationship by the level and kind of psychological empowerment (intrapersonal or interactional) on a parent experiences. Intrapersonal empowerment is related to self-efficacy, perceived competence, and desire for control, while interactional empowerment is related to an individual’s engagement in collective action and interactions with others. We find that active use of parental mediation increases intrapersonal empowerment resulting in parental mediation of social media influencers but has no effect on their positive or negative views on social media influencers. Moreover, passive use of social media results in interactional empowerment but has no significant impact on parental mediation but is related to positive views of social media influencers. Implications for regulators, practitioners, and parents are then discussed.